Enhanced performance in phenol removal from aqueous solutions by a buoyant composite photocatalyst prepared with a two-layered configuration on polypropylene substrate. Issue 1 (March 2016) - Tu, Wenting; Lin, Yi-Pin; Bai, Renbi
Highlights: PAC was tightly anchored on PPG surface by a thermal bonding process. TiO2 layer was loaded on immobilized PAC through a suspension hydrothermal deposition method. Layered configuration increased stability and synergistic effect of prepared composite photocatalyst. Developed composite photocatalyst was effective in phenol removal and in repeated use. Abstract: A buoyant composite photocatalyst was prepared by immobilizing powdered activated carbon (PAC), followed by TiO2 nanoparticles (P25), in a two-layered configuration on the polypropylene granule (PPG) substrate. The PAC layer was anchored onto PPG surface through a thermal bonding process, and then the P25 layer was loaded on the PAC layer by a suspension deposition method. The PAC layer not only served as a protection layer for PPG but also provided the composite photocatalyst with adsorptive property to enhance its capability of collecting organic pollutants from the solution and thus enhance the photocatalytic degradation efficiency. The performance of the prepared composite photocatalyst was evaluated through a series of experiments, including its stability against mechanical attrition and photocatalytic degradation, its adsorptive performance and photocatalytic degradation efficiency in phenol removal. The results showed that the developed composite photocatalyst (denoted as PPG-PAC-P25) was much more mechanically and photocatalytically stable, as compared to those composite photocatalysts prepared from immobilizing a mixture of PAC and P25 together on the PPG, and also showed better photocatalytic degradation performance in phenol removal. A synergistic effect was clearly observed with the composite photocatalyst that had the two layered PAC and P25 configuration. PPG-PAC-P25 was also tested for 20 recycles in a batch process for phenol removal and the overall photocatalytic degradation performance was only slightly decreased by less than 7%, indicated that the developed buoyant composite photocatalyst in this study has a great prospect for possible actual applications in the removal of organic pollutants from water or wastewater.